LACTOSE INTOLERANCE: NUTRITIONAL CONDUCT IN EARLY CHILDHOOD CARE - de Andrade Brandão, Miriam; Lúcio Dantas, Janaína; Kerlly Lopes da Silva, Rauana (Health and Society, 2023)
Introduction: Lactose intolerance in children in early childhood has been increasing the level of intolerance, evidencing in the child’s growth and development phases, being vital during the consumption of milk. Presenting symptoms and food discomfort due to the consumption of milk. Lactose intolerance can be classified as primary, when there is an intrinsic defect of the enzyme; or secondary, when there is a damage to the intestinal mucosa with consequent lack of it. Objective: This research aims to describe the conduct of the nutritionist towards children with lactose intolerance in early childhood based on literary reports. Method: Study of integrative literature review, descriptive and exploratory, with the purpose of presenting issues related to nutritional conduct in the care of children in early childhood. For this, information will be selected in other articles, found on search sites: SCIELO, PubMed and Google Scholar. The sample population will be composed of articles recently published between the years 2016 to 2020, and in accordance with the pre-established inclusion and exclusion criteria. The selection will take place in the month of May 2021. Results. It was found among the investigated productions that most of them are about nutritional characteristics, including the concern with calcium deficiency and alternatives to substitute products that develop symptoms by those that have low lactose content. Among the metabolic aspects were not the main focus of the articles found, however, only one article addressed this topic. Conclusions: Therefore, nutritionists play a fundamental role in the improvement and quality of life of children in early childhood, which will collaborate for their growth and healthy development, under the conditions presented, to provide information to parents about diseases and nutritionally adequate substitutes.